Second Century Trauma to the Eye - Appenzeller, Otto (British Journal of Healthcare and Medical Research, 2024)
We scrutinized several mummy portraits and found one with evidence of trauma to the left eye. This is the first evidence from the second century AD to show that children were beaten perhaps for disciplinary reasons then and now. Why the trauma to the eye occurred in this girl will forever remain a mystery.